Synthesis and Photophysical Properties of Vinyl-conjugated o-Carborane–isoxazole Dyads - Idrisov, Tair A.; Moseev, Timofey D.; Varaksin, Mikhail V.; Belyaev, Nikolay A.; Tsmokalyuk, Anton; Charushin, Valery; Chupakhin, Oleg N.; Bakulev, Vasiliy (Synthesis, 2025)
A metal-free synthetic strategy based on the cycloaddition reaction of oxamoyl chlorides to vinylacetylene o-carborane toward photoactive molecular systems bearing both vinyl-conjugated C-substituted o-carborane and isoxazole moieties is reported. The elaborated compounds exhibit absorption in the range of 250–300 nm with ε > 104 cm–1·M–1, but their emission varies greatly depending on the type of substituent at the C3 position of the isoxazole and does not demonstrate the solvatochromic characteristics typically associated with classical push–pull fluorophores. Incorporation of methoxy groups into the o-carborane–isoxazole dyads allows the design of an acceptor–π-conjugation–donor system (A–π–D), which is more efficient in light of intermolecular charge transfer (ICT) effects compared to the similar 1,2,3-triazole ones. Photoactive molecules with p-chlorophenyl and 2-(trifluoromethoxy)phenyl substituted in toluene have intense emissions of TICT states and PLQY up to 91%. Meanwhile, the 2-naphthyl-substituted molecule demonstrates dual-emission behavior in the 330–560 and 660–800 nm region with QY of 83 and 62%, respectively. Thus, the cycloaddition reactions of N-centered 1,3-dipoles to vinylacetylene o-carborane can be regarded as a promising synthetic approach in the design of advanced materials.
Keywords: o-Carborane; Isoxazole; 1,3-Dipolar cycloaddition; Fluorophores; Intermolecular charge transfer